Antecedents of Residents’ Pro-tourism Behavioral Intention: Place Image, Place Attachment, and Attitude - Shen, Ke; Geng, Chuan; Su, Xinwei (Frontiers in Psychology, 2019)
Few prior studies have investigated place image from residents’ perspective, how this and residents’ place attachment influence attitude to tourism, and consequent reactions. Accordingly, this study aims to develop a model for local residents’ pro-tourism behavioral intention, and to discover the relationships between constructs. Analysis was based on a sample of 370 residents in Huangshan City, China. Results indicate that residents’ attitude to tourism positively affects their pro-tourism behavioral intention. Residents’ place image is found to positively relate to place attachment and attitude to tourism, while place attachment is also related to attitude and pro-tourism behavioral intention. In addition, attitude to tourism mediates place image’s and place attachment’s respective relationships with pro-tourism behavioral intention. Lastly, place image indirectly impacts residents’ attitude to tourism and pro-tourism behavioral intention through place attachment. However, the positive relationship between place image and pro-tourism behavioral intention is not supported. Theoretical and practical implications are discussed.